Bimtek Penyusunan Laporan Arus Kas Berbasis Excel pada Kopwan Syariah Bumdes Sumbersuko Dampit Malang - Wibowo, Doni Teguh; Handayani, Sri; Sinollah (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2025)
One of the independent businesses owned by Sumbersuko Village is BUMDes with the most promising business unit being the Sharia Cooperative unit, especially in savings and loan activities. In order to support good BUMDes governance, improvements still need to be made in the future, financial management activities that have not been running well according to bookkeeping and financial reporting rules are seen from the bookkeeping and/or accounting side. The importance of the role of the BUMDes core management is also not optimal, skilled personnel in computer technology are also still relatively low, thus hampering the progress of BUMDes management. Transaction recording that still requires training so that it can meet the accounting standards used and BUMDes reporting regulations must be maximized again through training with other competent parties. The use of excel-based cash flow reports is expected to help better management